IP Cameras Beyond Security: A Systematic Literature Review Examining Their Adoption and Potential in the Healthcare Industry - Ong, Aldrin Patrick L.; Tomas, John Paul Q.; Tomas, Mary Christine A. (International Journal of Membrane Science and Technology, 2023)
There is a growing interest of IP Camera usage in the healthcare industries. IP Cameras are now being used in healthcare including patient monitoring, healthcare, telemedicine, etc. This paper aims to determine the applications of the IP Camera in the healthcare industry including how it is used in these applications to serve as a tool for future researchers to understand how they can use IP cameras in their future endeavors. A total of 31 related literatures and studies published from 2019 to 2022 were gathered, all of which used IP cameras in their specific studies. A code for each study was created according to their specific application and use. Results show that IP cameras were mainly used in 12 applications, mostly for Deep Learning, Robotics, and COVID-19 Application. These cameras were also used in 7 roles, mainly remote monitoring, telemedicine, telerehabilitation, and capturing data for model training, testing, and use. Overall, this study showed that IP cameras play a crucial role in the healthcare industry and have the potential to improve and revolutionize the way healthcare services are delivered such as improving telemedicine and promoting the use of telerehabilitation. Future research includes examining the use of IP cameras in other industries, especially in smart home environments, how IP cameras are used in different deep learning algorithms, and analyzing the benefits and challenges of IP cameras in different applications. CCS CONCEPTS: CCS CONCEPTS -> General and reference ~ Document types ~ General literature ACM Reference Format: This block will be automatically generated when manuscripts are processed after acceptance.